Optimum Management of Basrah Coastal Aquifer Use under Seawater Intrusion - Al-Suraifi, Ammar A. Akesh; Al-Kadhumi, Ahmed M. (Basrah Journal for Engineering Sciences, 2015)
This study presents an attempt for establishment of sustainable development and management policies for utilization of Basrah coastal aquifer. The simulation/optimization approach is used with application to Um-Qasr aquifer in Basrah. In this research, 5 management schemes for sustainable use of a coastal aquifer exposed to seawater intrusion were developed and solved. The objective of the management models is to maximize the total amount of water pumped from the aquifer for beneficial use, and optimum location, numbers and redistribution of wells. Salt concentration of the pumped water from each of the pumping well was considered as a main constraint together with the minimum water head which is considered to control saltwater intrusion by heads balances with time. Solutions of the management schemes are based on a linkage between a simulation module SEAWAT and Simulated Annealing (SA) algorithm optimization module. The heads and concentrations, calculated by the simulation model based on pumping rates, are used in a SA optimization procedure to achieve an optimum solution. The five multi-objective management schemes were applied on Um-Qasr coastal aquifer. The results show that using simulation / optimization approach in Um- Qasr region can improve planning and management policies and can give better decision for aquifer utilization. The results show that the aquifer can safely increase its pumping rate by (175%) greater than its current abstraction according to the results of schemes 1.